BAHASA AGAMA DAN DAKWAH ISLAM - Alfadhilah, Jauharotina; Fahrudi, Emi (Department of Da'wah Management, Faculty of Da'wah, IAINU Tuban, 2023)
Abstract The language of religion is the language used in any religion. One of the main characteristics of religious language, as stated by Ramsey, is the commitment and religious moral response of the speaker, because language and religious expression are very complex, as complex as thoughts, feelings and human activities themselves. Humans try to describe everything around them with symbols, icons, or metaphorical expressions to make it easier for them to understand the natural surroundings and establish communication between humans. Not only trying to communicate with each other, humans also try to understand things that are metaphysical, such as God, holy books and also religious rituals. These three things are often summarized in a term, namely the language of religion. Religion which is abstract and metaphysical requires humans to start thinking about these things by expressing them through iconic language. Icons and symbols that are often used are symbols that are still related to things of the senses. This is deliberately done so that humans can understand existence that is abstract and cannot be reached by the senses to be easy to understand and acceptable. If this very complex religious language is related to Da'wah Islamiyah, it will become a new challenge in the world of Islamic da'wah. Islam as a religion that is moderate and highly upholds tolerance, is certainly easier to accept anything that is formulated by religious language, provided that it does not come out of the Al-Qur'an or As-Sunnah.